The clinical effects of resveratrol on atherosclerosis treatment and its effect on the expression of NADPH oxidase complex genes in vascular smooth muscle cell line - Lixia, Guo; Haiyun, Zhao; Xia, Zheng (Cellular and Molecular Biology, 2021)
Atherosclerosis is a disease that covers the arteries of the middle to large arteries and can affect the aorta to the coronary arteries. Atherosclerosis is a progressive and slow process that begins in childhood and leads to clinical manifestations in adulthood. Increased activity of the NADPH oxidase complex plays an important role in the development of this complication. In this study, the clinical effects of resveratrol were considered on atherosclerosis treatment and its effect on the expression of NADPH oxidase complex genes was performed in the vascular smooth muscle cell line. For this purpose, 120 Chinese Patients prone to atherosclerosis participated for 12 months. These patients were divided into two groups of 60 patients. The first group was treated to the placebo and the second group was treated to 100 mg/day resveratrol for 12 months. Also, the expression of gp91Phox and P22Phox subunits of NADPH oxidase complex was evaluated in vascular smooth muscle cells by real-time PCR technique. The results showed that resveratrol could decrease systolic blood pressure, diastolic blood pressure, cholesterol, triglyceride, and low-density lipoprotein (LDL). It was also able to reduce the expression of gp91Phox and P22Phox subunits of NADPH oxidase complex in the vascular smooth muscle cell line. Therefore, it is possible to introduce resveratrol as an able medicine to treat atherosclerosis. However, more studies are needed to complete the information about the role of resveratrol.